Deterioro institucional en Venezuela como factor asociado a la emergencia de la delincuencia - Jesus García-Martínez (Revista Iberoamericana de Estudios de Desarrollo, 2018)
The article analyzes the singularity of the criminal phenomenon in Venezuela, due to the incidence of ideological and political variables in the increase of criminal rates. From this point of view, the etiology of criminal activity is associated rather with the progressive deterioration of political, social and judicial institutions, whether due to incompetence, indifference or complicity in crime. The same State, through its action of government, is creating those ideological, legal or cultural conditions that justify and protect the violation of the established legal norm. Given a situation of structural anomie created precisely by who should ensure the social order and governance of the country, this political legitimacy of violence favors both the arbitrariness of power that carries out a sectarian use of force with merely political aims, such as the manifest impunity of criminal activity.